Which lender of last resort for the eurosystem? - Otto Steiger (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2004)
The paper want to demonstrate how to organise central banking in a monetary union of independent nations, with emphasis on the role of the central bank as lender of last resort. Section I presents the first proposal for a decentralised central banking system in a monetary union by the Swedish economist Erik Lindahl in 1930, as well as that in 1989 for the Eurosystem, the centrepiece of European Monetary Union (EMU), by Carlo Ciampi, then President of the Banca d'Italia. Both proposals emphasised the necessity of a strong and powerful central monetary authority. Section II demonstrates that EMU lacks a central monetary institution, because the European Central Bank (ECB) is neither a bank of issue nor can it act as a lender of last resort. Section III discusses how to overcome this fundamental deficiency of the Eurosystem, arguing that the missing central fiscal authority in EMU is as much an Achilles heel as the “narrow” ECB.
Keywords: E58; E63; 330